The Relationship Between Early Marriage and Parenting Styles for Children Aged 3-5 Years - Yastutik, Baiq Wiwik; Sulaiman, Lalu; Khalik, Lalu Abdul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to investigates the link between early marriage and parenting styles among parents of children aged 3-5 years in Awang Village, Central Lombok, Indonesia. This study employs an observational analytic design with a cross-sectional approach. Data were gathered from 42 mothers who married before the age of 20. The research instrument is a questionnaire to collect information about socio-demographic and parenting style information, categorized as democratic, authoritarian, and permissive. Data analysis was conducted in two stages: univariate and bivariate analysis. The results of this study are that (1) a significant association between early marriage and authoritarian parenting styles, with 55% of mothers who married at or below 15 years old displaying authoritarian behavior, and 80% exhibiting permissive tendencies, (2) democratic parenting was exclusive to mothers who married at 16 years or older. Higher education levels were linked to democratic parenting, (3) a significant relationship between early marriage and authoritarian parenting, proven by statistical analysis using Fisher’s Exact Test (p = 0.001). The results suggest that early marriage leads to less supportive and more controlling parenting practices, negatively impacting child development. Thus, addressing socio-economic factors and improving educational opportunities are vital to mitigating the adverse effects of early marriage on parenting styles and child development.